Enhancement of Organizational Commitment among Management Trainee Graduates: The Influence of Training, Career Development, and Work-Life Balance Mediated by Work Motivation - Sinaga, Boy Andika; Utomo, Kabul Wahyu; Rahayu, Heffi Christya (GoAcademica Research & Publishing, 2024)
Organizational commitment is a critical variable in reducing employee turnover intentions. Enhancing organizational commitment can be facilitated through factors such as training, career development, work-life balance, and work motivation. The objective of this research is to identify the significant direct impact of training, career development, and work-life balance on organizational commitment and work motivation, as well as to demonstrate the significant indirect impact mediated by work motivation between training, career development, and work-life balance on organizational commitment. This study was conducted on staff employees who are graduates of the Management Trainee program at Company Group X, with a sample size of 202 respondents, utilizing probability sampling techniques. The independent variables in this study include training (X1), career development (X2), and work-life balance (X3), while the mediating variable is work motivation (Z), and the dependent variable is organizational commitment (Y). The research data were analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method with Likert scale measurements. The hypothesis testing results indicate a positive and significant influence of training (X1), career development (X2), work-life balance (X3), and work motivation (Z) on organizational commitment (Y), as well as a positive and significant influence of training (X1), career development (X2), and work-life balance (X3) on work motivation (Z). The indirect influence hypothesis test shows that training (X1), career development (X2), and work-life balance (X3) have a positive and significant effect on organizational commitment (Y) mediated by work motivation (Z).